Regulating Li-ion solvation sheath via dual-anchoring fluorinated copolymer networks for high-performance deep eutectic lithium metal batteries - Chenjun Ju; Enmin Li; Huanming Wei; Bingqi Jiang; Yiqi Wang; Zhenglong Yang (Chemical Engineering Journal, 2026)

Advancing precision nutrition beverages through plant-derived extracellular vesicles nanocarriers: A critical review of engineering strategies and functional mechanisms - Mi Li; Yuanchang Cao; Yunge Zhang; Peng Fei; Yanli Ma; Qisen Xiang; Yujun Jiang; Jian Ju; Cuicui Li (Trends in Food Science & Technology, 2026)

Lower crustal modification at the margin of the North China Craton: Multi-proxy geochemical and isotopic imaging constraints from the Late Mesozoic granitoids in Jiaodong Peninsula - Can-Can Wang; Li-Qiang Yang; Xue Gao; Wen-Yan He; Lei Ju; Dong Xie; Long Wang; Shi-Yao Zhai; Wei Yang; Nan Li; Zheng-Jiang Ding; Jun Deng (Journal of Asian Earth Sciences, 2026)

Mechanism-anchored ecological risk assessment of phthalates in coastal waters: Bridging environmental fate and molecular toxicity via an AOP framework - Shao-Yang Bu; Li-Ju Tan; Yan-Shan Chen; Kun Lin; Jiang-Tao Wang (Marine Pollution Bulletin, 2026)

Corrigendum to “Dual-surface sulfided Cu2O nanoreactor enabling near-unity selective photocatalytic CO2-to-ethanol” [Chem. Eng. J. 540 (2026) 177530] - Shiqi Zhang; Jingheng Li; Dingzhou Xiang; Chenghuan Zhong; Xiangxiang Wu; Ziyang Yu; Xing Wang; Hai Wu; Ju Wu; Zhuo Jiang; Shan Gao (Chemical Engineering Journal, 2026)

HOXC9 promotes cell proliferation and suppresses mitochondria-dependent apoptosis through the AKT/mTOR pathway in esophageal squamous cell carcinoma - Xinya Yu; Yajun Wang; Xinyu Ju; Zhen Li; Jieli Song; Boning Wu; Qi Ding; Yuan Jiang; Yupeng Wu (Molecular and Cellular Biochemistry, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Prediction of solute transport in three-dimensional rough-walled rock fractures: The role of geometrical heterogeneities - Na Huang; Zhenhui Wang; Yujing Jiang; Ju Wang; Bo Li (Journal of Hydrology, 2026)

Probing oxidation of hydroxy-polycyclic aromatic hydrocarbons at air-water interface in water microdroplets - Xiaohui Shi; Jiahui Huang; Siyu Zhu; Yuexin Zhang; Pei Liu; Bo Li; Hong Zhang; Yun Ju; Jing Zhao; Jie Jiang; Jing He (Journal of Hazardous Materials, 2026)

Accelerating high-fidelity debris-flow modeling with a super-resolution deep-learning framework - Yunhong Lv; Jian He; Luyu Ju; Ruochen Jiang; Yuran Li; Zening Zhao; Yuanen Pang; Limin Zhang (Engineering Geology, 2026)

Two decades of methane budgets at the sub-national scale in China - Pengfei Zhao; Zhen Zhang; Guanghui Huang; Zhenxuan Wang; Josep G. Canadell; Philippe Ciais; Huilin Chen; Shengqian Chen; Jason Blake Cohen; Fan Dai; Peng Gong; Robert B. Jackson; et al. (Science Bulletin, 2026)

Dual-surface sulfided Cu2O nanoreactor enabling near-unity selective photocatalytic CO2-to-ethanol - Shiqi Zhang; Jingheng Li; Dingzhou Xiang; Chenghuan Zhong; Xiangxiang Wu; Ziyang Yu; Xing Wang; Hai Wu; Ju Wu; Zhuo Jiang; Shan Gao (Chemical Engineering Journal, 2026)

DeepLrn-Source: Deep learning powered landslide source identification - Lu-Yu Ju; Ze-Ning Zhao; Shi-Hao Xiao; Yuan-En Pang; Jian He; Yun-Hong Lv; Ruo-Chen Jiang; Xin He; Li-Min Zhang (Engineering Geology, 2026)

Bedding-parallel fractures in shale: Formation mechanisms, geological significance, and implications for hydrocarbon accumulation—A review - Shu Jiang; Huanquan Sun; Jichao Fang; Hanyong Bao; Zhiguo Shu; Jiqing Li; Yiwen Ju (Earth-Science Reviews, 2026)

Intercellular Mitochondrial Transfer as Endogenous Neuroprotection: Mechanisms and Therapeutic Implications in Ischemic Stroke - Yun-Fan Zhang; Di Zhao; Jing-Jing Wei; Xiao Liang; Liu-ding Wang; Jia-Wei Wang; Li-bin Jiang; Ju-Ying Chen; Yun-Ling Zhang; Yue Liu (Translational Stroke Research, 2026)

Association of plasma n-3 polyunsaturated fatty acid with gut mycobiome and implications for glucose homeostasis - Congmei Xiao; Yue Xi; Xinyu Wang; Chang Gao; Ruiqi Shi; Zelei Miao; Yuhui Liang; Wanglong Gou; Ke Zhang; Chun Wang; Xinxiu Liang; Meng Ye; et al. (Science China Life Sciences, 2026)

Characteristics of structural superimposed halo at the Jiawula Ag-Pb-Zn deposit, Inner Mongolia, China and its significance for exploration - Xin-yu Gao; Gui-yuan Sun; Kang Wang; Wei Zhang; Zhi-ping Li; Wen-ju Li; Jiang Wei; Lin Yang; Hong-zhe Xie; Zi-wen Yang; Chao Ma (Journal of Geochemical Exploration, 2026)

Targeting angiopoietin-like protein 3 and interleukin-1β alleviated liver and kidney injury through attenuation of lipotoxicity and regulation of glycolipid metabolism in db/db mice - Shuwen Xu; Longfei Wang; Zihan Dou; Xiaozhi Hu; Zhonglian Cao; Yuanzhen Zhang; Xianhan Jiang; Tao Wu; Zhuojin Li; Yanyang Nan; An Zhu; Yu Bai; et al. (Inflammation Research, 2026)

Ice-covered lakes, hidden threats: Seasonal fate and risks of antibiotics and PAHs - Jie li; Peixin Wang; Lili Jiang; Hanyu Ju; Xuemei Liu; Guangxin Zhang; Erik de Goede; Jingjie Zhang (Water Research, 2026)

Tuning crystal structures of Mn nanomaterials on Enteromorpha prolifera biochar to enhance seawater purification - Guiping Jiang; Yingchao Li; Xianshuai Niu; Hanqi Liu; Xiaobo Wang; Kunpeng Dou; Jun Wang; Peng Ju (Journal of Environmental Management, 2026)

Insignificant future changes in decadal variability of East Asian summer monsoon rainfall - Juan Li; Haifeng Ju; Yeyan Jiang; Shanshan Zhong; Zhiwei Zhu (Climate Dynamics, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Structure–performance relationships and mechanism of lithium adsorption on Fe-based MOFs - Tianyu Li; Chengyu Huangfu; Huiqun Ju; Yumeng Jiang; Anni Yang; Jiafei Lyu; Xianghai Guo (Desalination, 2026)

Cooperative capture of NH₃ by –OH/–SO₃H functionalized porous organic polymers - Lu Zheng; Saisai Ju; Xiong Li; Yongde Ma; Hongwei Zhang; Zhenping Cai; Yanning Cao; Kuan Huang; Lilong Jiang (Chemical Engineering Journal, 2026)

Enhancing erythromycin production by Saccharopolyspora erythraea E3::sucBA in chemically defined medium - Xiang Ke; Shuohan Wang; Xing Jiang; Xu Li; Ju Chu; Xiwei Tian (Bioresource Technology, 2026)

Integrated surface-enhanced Raman spectroscopy and machine learning for identification and quantification of multi-target pesticide residues in fruit juices - Shen Jiang; Qiuyun Li; Xubin Quan; Yaowen Xing; Yujiang Huang; Xuming Mu; Yitong Meng; Guangrun Wu; Tong Ju; Yuhan Chu; Ruiyao Ma; Jing Wu; et al. (Food Chemistry, 2026)

A co-derived fluorinated SEI via chemical prelithiation toward stable and high-energy silicon-based lithium-ion batteries - Zhan Wang; Zhongyuan Feng; Shuang Li; Gaoyu Zhou; Quanchao Zhuang; Zhicheng Ju; Jiangmin Jiang; Huaiyu Shao (Chemical Engineering Journal, 2026)

Multiscale simulation of SiO2 nanoparticle evolution in coaxial premixed combustion reactors - Jie Ju; Lingli Luo; Yingjie Wu; Qilin Cheng; Hao Jiang; Yanjie Hu; Chunzhong Li (Chemical Engineering Journal, 2026)

Hierarchical photo-responsive glyco-metal covalent organic framework as a smart dual-enzyme platform for spatiotemporally controlled pathogen recognition-capture-inactivation and biofilm eradication - Zhengxuan Pan; Yan Jiang; Gentao Li; Jiayi Ju; Tianshui Xue; Jinbao Tang; Baolong Zhou (Chemical Engineering Journal, 2026)

Unveiling the synergistic mechanisms of multi-ionic removal in microbial desalination cells: Ion transfer, electrochemical behavior and microbial response - Chongtao Liu; Ran Ju; Chunxiao Han; Zhuangzhuang Liu; Yangyang Li; Xiaomei Jiang; Ling Wang; Yunfan Yang; Houkai Wu; Xiuping Tao (Bioresource Technology, 2026)

Exploring the mediating role of oxidative stress in the relationship between PM2.5 components and adverse pregnancy outcomes: Impacts on nucleic acids, proteins, and lipids - Yan Jiang; Deyan Wu; Yuqi Guo; Jia Xu; Hongjuan Liu; Aifeng Jia; Chen Li; Duan Ju; Liqiong Guo; Xueli Yang; Qiang Zhang; Bin Han; et al. (Atmospheric Pollution Research, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Gene expressions in newborns and the association with prenatal exposure to phthalate plasticizers – The Taiwan Maternal and Infant Cohort Study (TMICS) - Yi-Ju Wu; Hui-Ju Wen; Chung-Hsing Chen; Shin-Fen Tsai; Shih Sheng Jiang; Shu-Li Wang (Journal of Hazardous Materials, 2025)

Morphological evolution of the Arctic Tiksi coastline and driving mechanisms - Jixin Sun; Ze Zhang; Qingkai Yan; Xianglong Li; Andrei Zhang; Mengyao Ju; Xinyue Jiang (Geomorphology, 2025)

Lotus-leaf-bioinspired biomass-based films for intelligent /active packaging - Huie Jiang; Peng Guo; Haiyan Ju; Zhijian Li; Lijuan Chen; Haizhen Mo; Xinhua Liu (Food Chemistry, 2025)

Molecularly orchestrated room-temperature phosphorescent biocomposite for intelligent food packaging: Integrating anti-counterfeiting and real-time visual freshness supervision - Huie Jiang; Lanxue Zou; Zhijian Li; Peng Guo; Haiyan Ju; Haizhen Mo; Xinhua Liu (Food Packaging and Shelf Life, 2025)

Harnessing respiratory chain engineering enhances erythromycin production in Saccharopolyspora erythraea employing chemically defined medium - Xing Jiang; Yazhi Liu; Shuohan Wang; Xiang Ke; Qinghai Shang; Feng Li; Zhenhua Yu; Xu Li; Xiwei Tian; Ju Chu (Chemical Engineering Journal, 2025)

Balancing nitrogen metabolism to efficiently drive anti-tuberculosis ilamycins biosynthesis in Streptomyces atratus - Gaofan Zheng; Weiyan Zhou; Yingyue Gui; Yuxi Jiang; Yunfei Zhu; Junying Ma; Jianhua Ju; Xiujuan Xin; Baoli Li; Ruida Wang; Ming Zhao; Faliang An (Bioresource Technology, 2025)

Analysis of hydraulic response characteristics of reservoir bank slope under the action of reservoir water level rise and fall - Shu-Jun Ju; Ming-Li Xie; Neng-Pan Ju; Liang Duan; Ming-Cheng Jiang; Yu-Feng He (Applied Geophysics, 2025)

The Association between Dietary and Circulating Copper Levels and Osteoporosis: a Scoping Review - Ye Ju; Wei Xiong; Yuqi Pang; Zilan Chen; Jiaojiao Hou; Sirui Zheng; Zihao Li; Ting Liu; Hongxia Xia; Maoyao Xia; Yangdan Zhong; Jiayuan Li; et al. (Biological Trace Element Research, 2025)
Copper plays a crucial role in osteoporosis by regulating osteoblast function, inhibiting osteoclast activity, and promoting bone matrix maturation. However, the epidemiological relationship between copper and osteoporosis remains inconclusive. This scoping review systematically examined the existing evidence on the association between dietary and circulating copper levels and bone related diseases with a special focus on osteoporosis. Studies were identified through comprehensive search of electronic databases from inception to January 2025. Eligible studies included randomized clinical trials, cohort studies, case-control studies, and cross-sectional studies involving human subjects and published in English. The review included 18 studies. For dietary copper, studies reported that higher intake was associated with improved bone mineral density (BMD). For circulating copper, studies reported that lower levels were associated with higher subsequent risk of osteoporosis and fractures. For environmental copper, exposed via drinking water or hair copper levels were not associated with osteoporosis. Current evidence on the relationship between copper and bone health remains largely consistent, suggesting a potential inverse association between copper levels and osteoporosis risk.

Hybrid fabrication of perfusable stiffness-flexible integrated scaffold mimicking hierarchical tubular bone - Yifan Zhang; Zhipeng Li; Bingkun Bao; Jingyi Ju; Wenbin Jiang; Linyong Zhu; Jiaming Sun; Zhenxing Wang (Chemical Engineering Journal, 2025)

Microstructure regulation of aerogels for wearable flexible pressure sensors - Xinyi Ju; Xueliang Jiang; Chu Yao; Danfeng Zhou; Huan Yang; Chenjian Li; Feng You; Zhi-Min Dang (Chemical Engineering Journal, 2025)

YY1 lactylation promotes fibroblast senescence by targeting the PU.1-BTG2 axis to promote oral submucous fibrosis - Muhammad Tufail; Jing Zhang; Cai-Yun He; Jia-Ju Hu; Jie Liang; Wen-Dong Wan; Yu-Qi Huang; Zhen Rao; Hong Wu; Can-Hua Jiang; Ning Li (Chemico-Biological Interactions, 2025)

Recent advances in Pyrazolo[3,4-d]pyrimidine-based dual inhibitors in the treatment of cancers - Hanrui Jiang; Nan Li; Ruosong Qin; Siyu Lin; Xuelian Wang; Chunyan Li; Jiwei Shen; Ye Chen; Ju Liu; Shi Ding (Molecular Diversity, 2025)

Calibration of the Edinburgh Elasto-Plastic Adhesion contact model for modelling clay-moist soil with high moisture content - Xuan Deng; Wencheng Wu; Jiawei You; Rui Jiang; Mengliang Li; Ju Li; Youfeng Tao; Hong Cheng; Wei Zhou; Fei Deng; Yong Chen; Wanjun Ren; et al. (Computers and Electronics in Agriculture, 2025)

Dietary valine modulates hepatic immune responses in largemouth bass (Micropterus salmoides) against Aeromonas veronii infection: Integrated regulation of antioxidant defense, ER stress and autophagy - Ju Zhao; Xiaoqing Li; Tianran Zhang; Haifeng Liu; Quanquan Cao; Jun Jiang (Fish & Shellfish Immunology, 2025)

Destruction of the southern part of the North China Craton and its relationship with enrichment of shale gas in coal measures - Peng Wang; Yiwen Ju; Guofu Li; Shu Jiang; Jinchuan Zhang; Lei Xiao; Wei Wang; Jian Gao (Science China Earth Sciences, 2025)

The effects of pond purification system on intestinal function of channel catfish (Ictalurus punctatus): a focus on intestinal development, digestion and absorption, and junction integrity - Zhong-Bing Zheng; Yu Yang; Jun Liu; Ming-Cheng Zhou; Ju-Hua Li; Long-Jiang Tang; Hai-Long Nie; Kang-Sheng Chen; Feng Liu; Xiang-Ning He; Zhi-Yuan Lu (Frontiers in Marine Science, 2025)
Pond purification system (PPS) is an outdoor aquaculture system designed based on recirculating aquaculture system (RAS) principles, utilizing recirculating water technology, which can achieve large-scale fish farming in the recirculating water system. The purpose of this experiment is to investigate the alterations in growth performance, intestinal histology, digestion-absorption function, and structural integrity of channel catfish raised in PPS. The findings indicated a significant optimization in water quality indicators pertinent to aquaculture, including total nitrogen, total phosphorus, chemical oxygen demand (COD), ammonia nitrogen, nitrite, and dissolved oxygen. Additionally, the growth performance of channel catfish reared in the PPS group was markedly improved. The intestinal morphology of these channel catfish exhibited increased villus height and a reduced number of mucus cells. Furthermore, serum levels of diamine oxidase and D-lactic acid were significantly decreased in channel catfish raised in the PPS group, while the expression of genes related to the apical junction complex was significantly upregulated, suggesting improved intestinal structural integrity. Moreover, the activities of digestive and absorptive enzymes, such as trypsin, amylase, lipase, and Na + -K + -ATPase, were elevated, indicating enhanced digestive and absorptive functions. In conclusion, based on the conditions of this experiment, the pond purification system module used in this study can effectively improve the quality of the aquaculture water, enhance fish growth performance and improve their intestinal health.

Comparative analysis of phytoplankton community structure and stability in the Arabian Sea and Bay of Bengal using eDNA metabarcoding - Changwen Li; Ge Xiao; Han Long; Tongxi Ai; Fenghua Tang; Jianfeng Ju; Shenglong Yang; Yan Pi; Lei Gao; Lingbo Ma; Wei Fan; Ming Zhao; et al. (Marine Environmental Research, 2025)

Wide wall liquid film thickness distribution in narrow rectangular geometry for annular flow - Peng Ju; Xinhai Xu; Zhengqian Qi; Yi Qu; Baixuan Jiang; Peize Li; Takashi Hibiki (Annals of Nuclear Energy, 2025)

Sulfate-reducing bacteria-regulated Cu2O-doped Cu2S nanocubes as Fenton-like catalysts for efficient dye degradation and disinfection - Zihao Li; Chenlu Wang; Liuhui Zhao; Hongling Liu; Jing Yang; Xiaofan Zhai; Peng Ju; Quantong Jiang; Jizhou Duan; Baorong Hou (Journal of Environmental Chemical Engineering, 2025)

Effect of wave height on seismic fragility of subsea tunnels in sandy seabed - Ling-Yu Xu; Ju-Ping Xi; Jia-Wei Jiang; Fei Cai; Yong-Yi Li; Guo-Xing Chen (Ocean Engineering, 2025)

A flexible intelligent sensor for patients with amyotrophic lateral sclerosis - Lei Duan; Zhi Li; Fan Jiang; Zong-Ju Chen; Wei-Song Zhang; Pei-Chen Zhao; Li-Chun Wang; Yan-Long Luo; Che Zhao; Cheng-Hui Li (Chemical Engineering Journal, 2025)

Bonding of wood with high strength and excellent water resistant cellulose colloidal adhesives - Yuyan Jiang; Tian Ju; Liangxian Liu; Haiyu Li; Yue Zhang; Na Wang; Zetan Lu; Ming Wei; Dexiu Min; Yanjun Xie; Jian Li; Yonggui Wang; et al. (Chemical Engineering Journal, 2025)

Estimating maize root zone soil moisture by assimilating high spatiotemporal resolution optical and radar remote sensing into the WOFOST-HYDRUS coupled model - Lei Li; Xiaofeng Li; Xingming Zheng; Hanyu Ju; Xiaojie Li; Tao Jiang; Xiangkun Wan (Journal of Hydrology, 2025)

Highly efficient SF6 degradation solution based on CuO-ZnO with exceptional stability - Kexin Zhu; Fuping Zeng; Zhihui Li; Langlang Lv; Hua Jiang; Guangzhi Chen; Xiangyu Wang; Ju Tang (Journal of Environmental Chemical Engineering, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Evaluation of a transgenic tg(Hspa8b: GFP) Nile tilapia for monitoring of stress and anti-stress effects of the influence of temperature and vibration - Zhi Lei Yao; Jia Yue Li; Xiao Wang; Hong Ju Chen; Shi-Jin Jiang; Yan Zhao; Xiang Shan Ji (Aquaculture International, 2025)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Insight into structural changes in heat-induced whey protein-fucoidan hydrogel by SR-IR and molecular docking techniques - Huiyu Xiang; Zhimo Jiang; Weibing Tao; Siyi Lv; Yilong Li; Jirun Peng; Chenhao Wang; Hanxun Ju; Xiaomeng Sun; Chun Li (Food Research International, 2024)

Highly efficient removal and real-time visual detection of fluoride ions using ratiometric CAU-10-NH2@RhB: Probe design, sensing performance, and practical applications - Ping Ju; Wenhui Lu; Guixue Zhang; Shuping Wang; Anzhang Li; Qingxiang Zhang; Long Jiang; Ensheng Zhang; Fengli Qu (Journal of Hazardous Materials, 2024)

Distribution, characteristics, and ecological risks of microplastics in the Hongyingzi sorghum production base in China - Tianzhu Shi; Huajie Xu; Changbin Pan; Xiangui Wang; Yuting Jiang; Qiong Li; Ju Guo; Xinliang Mo; Pan Luo; Qilin Fang; Jing Yang (Environmental Pollution, 2024)

Thermophysical properties and energy-saving efficiency of phase change microcapsule foamed cement composite insulation materials - Lingyong Ma; Xinyue Zhao; Enmin Fu; Qing Li; Wei Jiang; Lidi Huang; Yongyi Zhang; Zhipeng Ju (Energy and Buildings, 2024)

Estimation of pollution sources and hydraulic conductivity field in a coastal aquifer under tidal effects - Chao Wu; Simin Jiang; Xuemin Xia; Yue Sun; Zhi Li; Mengdie Ju; Si Li; Shihui Liu (Marine Georesources & Geotechnology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Sesquiterpene lactones from Tithonia diversifolia with ferroptosis-inducing activities - Ao-Xue Ding; Yi-Ming Shan; Chen-Yue Li; Guo-Qing Qin; Tong Chen; Qing Wang; Xiang-Gang Hu; Peng-Ju Guo; Hai-Jun Yu; Wen-Qiong Wang; Li-Jiang Xuan (Phytochemistry, 2024)

Highly textured CMOS-compatible hexagonal boron nitride-based neuristor for reservoir computing - Haizhong Zhang; Jiayi Li; Xin Ju; Jie Jiang; Jing Wu; Dongzhi Chi; Diing Shenp Ang; Wei Hu; Rongshan Wei; Minmin Zhu; Xiaoqiang Lu (Chemical Engineering Journal, 2024)

Central cell: the key to determine persistent pollen tube attraction or termination - Jiang-Guo Meng; Shi-Zhen Li; Hong-Ju Li (Science China Life Sciences, 2024)

Angiotensin-Converting Enzyme Insertion/Deletion Polymorphism and the Risk of Leukoaraiosis in a South Chinese Han Population: A Case–Control Study - Dong-can Mo; Xiao-ju Wu; Xiao-ling Li; Liu-yu Liu; Yi-ying Jiang; Guo-qiu Zhou; Li-jie Chen; Jiao-xing Li; Man Luo (Biochemical Genetics, 2024)

Occurrence of microplastics in the Haima cold seep area of the South China Sea - Di Zhang; Jingxi Li; Peng Ju; Wei Cao; Fenghua Jiang; Chengjun Sun (Science of The Total Environment, 2024)

Preparation of Bi4Ti3O12/TiO2 by flame spray pyrolysis for photoelectrocatalytic degradation of tetracycline - Chenchen Li; Jing Lei; Xiucheng Gu; Jie Ju; Hao Jiang; Chunzhong Li; Yanjie Hu (Journal of Cleaner Production, 2024)

Inch-size and thickness-adjustable hybrid manganese halide single-crystalline films for high resolution X-ray imaging - Ming Zhou; Hongli Jiang; Tiankuo Hou; Shuo Hou; Jingyu Li; Xinyi Chen; Chuanqi Di; Jiawen Xiao; Huifang Li; Dianxing Ju (Chemical Engineering Journal, 2024)

High conductivity poly(meta-terphenyl alkylene)s proton exchange membranes for high temperature fuel cell - Xueqing You; Qing Ju; Yichang Ma; Guiqin Yi; Zhangtang Jiang; Nanwen Li; Qiugen Zhang (Chemical Engineering Journal, 2024)

Durability life evaluation of marine infrastructures built by using carbonated recycled coarse aggregate concrete due to the chloride corrosive environment - Han Jiang; Linjian Wu; Li Guan; Mingwei Liu; Xueli Ju; Zhouyu Xiang; Xiaohui Jiang; Yingying Li; Jia Long (Frontiers in Marine Science, 2024)
Due to the harsh marine environment of chloride ion invasion and corrosion, the issues of long-term chloride transport and durability life evaluation for marine infrastructures constructed/maintained by recycled aggregate concrete (RAC) after enhancement remain poorly understood. For our studies, an accelerated carbonation modification method for recycled coarse aggregate (RCA) was adopted to prepare carbonated recycled coarse aggregate (CRCA) samples, and the macroproperties, i.e., apparent density and water absorption, of CRCA were enhanced by approximately 1.40-3.97% and 16.3-21.8%, respectively, compared with those of RCA. An in-door experiment for chloride transport into concrete specimens subjected to a simulated marine environment of alternating drying-wetting cycles was conducted. The chloride profiles and transport characteristics of carbonated recycled coarse aggregate concrete (CRCAC), recycled coarse aggregate concrete (RCAC), and natural coarse aggregate concrete (NCAC) were analysed and compared. The results indicated that the chloride penetration depths and concentrations of CRCAC were approximately 52.6-96.2% of those of RCAC, which highlighted the better chloride resistance of CRCAC. A chloride transport model for marine concrete structures with various coarse aggregate types in a corrosive marine environment was established. Taking a certain harbour wharf as an example, the durability life of this case considering the application of the CRCAC was evaluated based on the chloride transport model, and the durability life of the CRCAC structure was improved by approximately 28.10% compared with that of the RCAC. The CRCAC developed in this paper has improved mechanical performance and durability than those of RCAC, and it has the potential to replace the NCAC and further support the construction and maintenance of marine infrastructures.

Effects of chronic low-level lead (Pb) exposure on cognitive function and hippocampal neuronal ferroptosis: An integrative approach using bioinformatics analysis, machine learning, and experimental validation - Yingsi Cao; Wenjing Zhao; Yanqi Zhong; Xiaofan Jiang; Huiya Mei; Yuanjin Chang; Dongqin Wu; JianRui Dou; Emely Vasquez; Xian Shi; Jiatao Yang; Zhongtang Jia; et al. (Science of The Total Environment, 2024)

Eighteen iridoids from the roots and rhizomes of Valeriana jatamansi and their protective effects against α-hemolysin - Yao Zhu; Peng-Ju Guo; Ao-Xue Ding; Liu Zheng; Gao-Xiang Du; Tong Chen; Guo-Qing Qin; Xiang-Gang Hu; Wen-Qiong Wang; Li-Jiang Xuan (Phytochemistry, 2024)

An innovative method for the efficient and selective extraction of Co, Ni, Cu, and Mn from oceanic cobalt-rich crusts by ammonium sulfate roasting: Behavior, roasting kinetics and mechanism - Jinrong Ju; Yali Feng; Haoran Li; Ruiyu Ma; Yunhao Li; Hongyu Zhao; Haoyu Wang; Shiwei Jiang (Minerals Engineering, 2024)

Atmospheric fate of typical liquid crystal monomers in the tropospheric gas, liquid, and granular phases - Yanru Huo; Zexiu An; Mingxue Li; Jinchan Jiang; Yuxin Zhou; Ju Xie; Jianguo Zhang; Maoxia He (Journal of Environmental Sciences, 2024)

Comparison of dye-based and probe-based RT-LAMP in detection of canine astrovirus - Haixiao Shen; Dequan Yang; Xin Li; Houbin Ju; Feifei Ge; Xianchao Yang; Jian Wang; Luming Xia; Hongjin Zhao; Ping Jiang (Archives of Virology, 2024)

Vitamin D3 activates the innate immune response and xenophagy against Nocardia seriolae through the VD receptor in liver of largemouth bass (Micropterus salmoides) - Quanquan Cao; Ju Zhao; Mingyao Yan; Zhong Luo; Fu Luo; Lin Feng; Weidan Jiang; Pei Wu; Yan Wang; Debin Li; Haifeng Liu; Jun Jiang (Aquaculture, 2024)

Adsorption of metal ions by oceanic manganese nodule and deep-sea sediment: Behaviour, mechanism and evaluation - Yunhao Li; Yali Feng; Haoran Li; Yisong Yao; Chenglong Xu; Jinrong Ju; Ruiyu Ma; Haoyu Wang; Shiwei Jiang (Science of The Total Environment, 2024)

Effect of pH on UV/H2O2-mediated removal of single, mixed and halogenated parabens from water - Yanru Huo; Mingxue Li; Zexiu An; Jinchan Jiang; Yuxin Zhou; Yuhui Ma; Ju Xie; Fenghua Wei; Maoxia He (Journal of Hazardous Materials, 2024)

Differences in the degradation behavior of disinfection by-products in UV/PDS and UV/H2O2 processes and the effect of their chemical properties - Yuhui Ma; Mingxue Li; Yanru Huo; Yuxin Zhou; Jinchan Jiang; Ju Xie; Maoxia He (Chemosphere, 2023)

Homogeneous and heterogeneous atmospheric ozonolysis of chlorobenzene:Mechanism, kinetics and ecotoxicity assessment - Nuan Wen; Mingxue Li; Yanru Huo; Yuxin Zhou; Jinchan Jiang; Yuhui Ma; Qingyuan Gu; Ju Xie; Maoxia He (Chemosphere, 2023)

Analysis of enrichment, correlation, and leaching patterns of rare earth elements in coal fly ash assisted by statistical measures - Tongyao Ju; Yuan Meng; Siyu Han; Fanzhi Meng; Li Lin; Jinglin Li; Jianguo Jiang (Science of The Total Environment, 2023)

Crushing characteristics and performance evaluation of iron ore in a cone crusher: A numerical study - Chuanning Jiang; Dazhao Gou; Chao Li; Guanyin Wu; Xizhong An; Ju Wang; Pengyue Guo (Minerals Engineering, 2023)

Tidal effects on carbon dioxide emission dynamics in intertidal wetland sediments - Jiang-Chen Gong; Bing-Han Li; Jing-Wen Hu; Xi-Ju Ding; Chun-Ying Liu; Gui-Peng Yang (Environmental Research, 2023)

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

Modeling China's terrestrial ecosystem gross primary productivity with BEPS model: Parameter sensitivity analysis and model calibration - Xiuli Xing; Mousong Wu; Wenxin Zhang; Weimin Ju; Torbern Tagesson; Wei He; Songhan Wang; Jun Wang; Lu Hu; Shu Yuan; Tingting Zhu; Xiaorong Wang; et al. (Agricultural and Forest Meteorology, 2023)

Emticicia fluvialis sp. nov., a potential hormone-degrading bacterium isolated from Nakdong River, Republic of Korea - Hyun-Sun Baek; Yong Guan; Min-Ju Kim; Yue Jiang; Mi-Kyung Lee; Ki-Hyun Kim; Jaeyoon Lee; Yuna Shin; Yoon-Ho Kang; Zhun Li (Antonie van Leeuwenhoek, 2023)

The complex role of air pollution on the association between greenness and respiratory mortality: Insight from a large cohort, 2009–2020 - Wenjing Wu; Zhicheng Du; Ying Wang; Yuqin Zhang; Shirui Chen; Xu Ju; Gonghua Wu; Zhiqaing Li; Jie Sun; Jie Jiang; Weihua Hu; Ziqiang Lin; et al. (Science of The Total Environment, 2023)

An efficient and clean method for the selective extraction and recovery of manganese from pyrolusite using ammonium sulfate roasting-water leaching and carbonate precipitation - Jinrong Ju; Ruiyu Ma; Yunhao Li; Yali Feng; Haoran Li; Haoyu Wang; Shiwei Jiang (Minerals Engineering, 2023)

Ent- kaurane diterpenoids from Isodon japonica var. glaucocalyx with PCSK9 inhibitory activities - Ge Wang; Tong Chen; Peng-Ju Guo; Shou Peng; Wen-Qiong Wang; Li-Jiang Xuan (Phytochemistry Letters, 2023)

Study on the effectiveness of ionic liquid-based biphasic amine solvent in removing H2S, NH3 and CO2 from biogas and its influential characteristics - Fanzhi Meng; Tongyao Ju; Siyu Han; Li Lin; Jinglin Li; Kailun Chen; Jianguo Jiang (Chemical Engineering Journal, 2023)

Microporous chitosan/polyvinyl alcohol based active packaging materials with integrated gas-transmission, radiation-cooling, anti-microbial, and ultraviolet shielding features - Jiang Huie; Zhao Suqiu; Ju Haiyan; Li Zhijian; Chen Lijuan; Li Nihao; Liu Xinhua (Chemical Engineering Journal, 2023)

Efficient removal of Cl-DBPs by direct-indirect continuous hydrodechlorination reduction reaction on Ti3C2X2 surface: A theoretical calculation - Yuxin Zhou; Tao Zhuang; Haijie Cao; Mingxue Li; Yanru Huo; Jinchan Jiang; Yuhui Ma; Ju Xie; Maoxia He (Chemosphere, 2023)

Remarkable bioactivity, bio-tribological, antibacterial, and anti-corrosion properties in a Ti-6Al-4V-xCu alloy by laser powder bed fusion for superior biomedical implant applications - Jiang Ju; Rui Zan; Zhao Shen; Chenchen Wang; Peng Peng; Jun Wang; Baode Sun; Bo Xiao; Qian Li; Shaofei Liu; Tao Yang (Chemical Engineering Journal, 2023)

Identifying nitrate sources and transformations in an agricultural watershed in Northeast China: Insights from multiple isotopes - Yao Wu; Hanyu Ju; Hao Jiang; Guangxin Zhang; Peng Qi; Zan Li (Journal of Environmental Management, 2023)

Liver fibrosis in fish research: From an immunological perspective - Quanquan Cao; Hongying Shan; Ju Zhao; Jinhe Deng; Man Xu; Hao Kang; Tong Li; Ye Zhao; Haifeng Liu; Jun Jiang (Fish & Shellfish Immunology, 2023)

A green and multi-win strategy for coal fly ash disposal by CO2 fixation and mesoporous silica synthesis - Tongyao Ju; Yuan Meng; Siyu Han; Fanzhi Meng; Li Lin; Jinglin Li; Yufeng Du; Mengzhu Song; Tian Lan; Jianguo Jiang (Science of The Total Environment, 2023)

Comprehensive study of recycling municipal solid waste incineration fly ash in lightweight aggregate with bloating agent: Effects of water washing and bloating mechanism - Siyu Han; Tongyao Ju; Fanzhi Meng; Li Lin; Jinglin Li; Kailun Chen; Jianguo Jiang (Science of The Total Environment, 2023)

Peak extraction and classification from digital elevation models based on the relationship between morphological characteristics and spatial position - Ming-wei Zhao; Yue Fang; Can-can Yang; Xiao-xiao Ju; Xiao-li Huang; Ling Jiang; Chun Wang; Yan Xu (Journal of Mountain Science, 2023)

Bioinformatic and functional analysis of OsDHN2 under cadmium stress - Wen-jun Jiang; Meng-ting Wang; Zhi-ye Du; Jia-hao Li; Yang Shi; Xin Wang; Long-ying Wu; Ji Chen; Min Zhong; Ju Yang; Bin-hua Hu; Jin Huang (Functional & Integrative Genomics, 2023)

Net-zero energy optimization of solar greenhouses in severe cold climate using passive insulation and photovoltaic - Wei Jiang; Yang Jin; Gongliang Liu; Zhipeng Ju; Müslüm Arıcı; Dong Li; Wei Guo (Journal of Cleaner Production, 2023)

The aomogeneous and heterogeneous oxidation of organophosphate esters (OPEs) in the atmosphere: Take diphenyl phosphate (DPhP) as an example - Yanru Huo; Mingxue Li; Jinchan Jiang; Yuxin Zhou; Yuhui Ma; Ju Xie; Maoxia He (Environmental Pollution, 2023)

Remediation of atrazine-contaminated soil in a fluidized-bed DBD plasma reactor - Nan Jiang; Ying Qu; Jinwei Zhu; Hongchang Wang; Ju Li; Yun Shu; Yutao Cui; Yuling Tan; Bangfa Peng; Jie Li (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Novel monoethanolamine absorption using ionic liquids as phase splitter for CO2 capture in biogas upgrading: High CH4 purity and low energy consumption - Fanzhi Meng; Tongyao Ju; Siyu Han; Li Lin; Jinglin Li; Kailun Chen; Jianguo Jiang (Chemical Engineering Journal, 2023)

The multiple roles of phenols in the degradation of aniline contaminants by sulfate radicals: A combined study of DFT calculations and experiments - Mingxue Li; Pijun Duan; Yanru Huo; Jinchan Jiang; Yuxin Zhou; Yuhui Ma; Zhehui Jin; Qiong Mei; Ju Xie; Maoxia He (Journal of Hazardous Materials, 2023)

Comparison of ribavirin degradation in the UV/H2O2 and UV/PDS systems: Reaction mechanism, operational parameter and toxicity evaluation - Jinchan Jiang; Zexiu An; Mingxue Li; Yanru Huo; Yuxin Zhou; Ju Xie; Maoxia He (Journal of Environmental Chemical Engineering, 2023)

Liquid flow and breakage behaviors of two liquid jets impacting on the wire mesh with different impinging angles - Zhong-Bo Sun; Hai-Long Liao; Li-Hua Wang; Lan Jiang; Xin Zhang; Bao-Ju Wang; Guang-Wen Chu; Yong Luo (Chemical Engineering Journal, 2023)

Characteristics, application and modeling of solid amine adsorbents for CO2 capture: A review - Li Lin; Yuan Meng; Tongyao Ju; Siyu Han; Fanzhi Meng; Jinglin Li; Yufeng Du; Mengzhu Song; Tian Lan; Jianguo Jiang (Journal of Environmental Management, 2023)

Zincophilic polymer semiconductor as multifunctional protective layer enables Dendrite-Free zinc metal anodes - Jiangmin Jiang; Zhenghui Pan; Jiaren Yuan; Jun Shan; Chenglong Chen; Shaopeng Li; HaiXu; Yaxin Chen; Quanchao Zhuang; Zhicheng Ju; Hui Dou; Xiaogang Zhang; et al. (Chemical Engineering Journal, 2023)

Correction to: Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/ TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Phenolic glycosides from Sanguisorba officinalis and their anti-inflammatory effects - Jin-feng Chen; Lu Tan; Feng Ju; Qi-xuan Kuang; Tian-long Yang; Fang Deng; Yu-cheng Gu; Li-shi Jiang; Yun Deng; Da-le Guo (Natural Product Research, 2022)

Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)
Sepsis can cause sepsis-associated encephalopathy (SAE), but whether SAE was induced or exacerbated by ferroptosis remains unknown. In this study, the rat sepsis model was constructed using the cecal ligation and puncture method. The blood–brain barrier (BBB) permeability was measured by Evans blue dye (EBD) in vivo. The levels of ROS, Fe ion, MDA, GSH, and GPX4 were assessed by enzyme-linked immunosorbent assay (ELISA). The exosomes isolated from serum were cultured with bEnd.3 cells for the in vitro analysis. Moreover, bEnd.3 cells cultured with 100 μM FeCl3 (iron-rich) were to simulate ferroptosis stress. The cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. A dual-luciferase reporter gene assay was performed to confirm the relationship between miR-9-5p with NEAT1, TFRC , and GOT1 . In vivo, it is found that BBB permeability was damaged in model rats. Level of ROS, Fe ion, and MDA was increased, and level of GSH and GPX4 was decreased, which means ferroptosis was induced by sepsis. Exosome-packaged NEAT1 in serum was significantly upregulated in model rats. In vitro, it is found that NEAT1 functions as a ceRNA for miR-9-5p to facilitate TFRC and GOT1 expression. Overexpression of NEAT1 enhanced ferroptosis stress in bEnd.3 cells. Increased miR-9-5p alleviated sepsis-induced ferroptosis by suppressing the expression of TFRC and GOT1 both in vivo and in vitro. In conclusion, these findings suggest that sepsis induced high expression of serous exosome-derived NEAT1, and it might exacerbate SAE by promoting ferroptosis through regulating miR-9-5p/ TFRC and GOT1 axis.

A dry powder inhalable formulation of salvianolic acids for the treatment of pulmonary fibrosis: safety, lung deposition, and pharmacokinetic study - Linxia Jiang; Yijun Li; Jiaqi Yu; Jianhong Wang; Jiarui Ju; Jundong Dai (Drug Delivery and Translational Research, 2021)

Chthonobacter rhizosphaerae sp. nov., a bacterium isolated from rhizosphere soil of Citrus sinenesis - Xiu-Ming Liu; Xing-Kui Zhou; Yuan-Dong Li; Ju-Xing Jiang; Li-Min Dong; Bao-Zhu Fang; Wen-Jun Li; Yan-Qing Duan (Archives of Microbiology, 2021)

Nitrification characteristics of long-term idle aerobic activated sludge during domestication - Zhaoxu Peng; Tianyu Lou; Kun Jiang; Ningqi Niu; Ju Wang; Lei Li (Environmental Science and Pollution Research, 2021)

Associations between SNP83 of phosphodiesterase 4D gene and carotid atherosclerosis in a southern Chinese Han population: a case–control study - Liu-yu Liu; Dong-can Mo; Jian-li Li; Yi-ying Jiang; Guo-qiu Zhou; Dong-dong Jiang; Li-jie Chen; Xiao-ju Wu; Jiao-xing Li; Man Luo (Mammalian Genome, 2021)

Epidemiological and clinical analysis of the outbreak of dengue fever in Zhangshu City, Jiangxi Province, in 2019 - Jingen Wang; Qiubo Chen; Zhongbao Jiang; Xiaoju Li; Huiping Kuang; Ting Chen; Feng Liu; Wujuan Zhou; Yanxia Huang; Yong Luo; Jianfeng Rao; Weihua Ju; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Initial chest CT findings in COVID-19: correlation with clinical features - Zhu-jing Shen; Nan Lu; Lu-lu Gao; Jian Lv; Hua-fu Luo; Ji-feng Jiang; Chao Xu; Shi-ya Li; Ju-jiang Mao; Kai Li; Xiao-pei Xu; Bin Lin (Journal of Zhejiang University-SCIENCE B, 2020)

Advances in Urban Meteorological Research in China - Shiguang Miao; Weimei Jiang; Ping Liang; Hongnian Liu; Xuemei Wang; Jianguo Tan; Ning Zhang; Ju Li; Wupeng Du; Lin Pei (Journal of Meteorological Research, 2020)

Polyploidization of Plumbago auriculata Lam. in vitro and its characterization including cold tolerance - Yulan Jiang; Shiliang Liu; Ju Hu; Guangti He; Yingqi Liu; Xi Chen; Ting Lei; Qiao Li; Lijuan Yang; Wenji Li; Di Hu; Jiani Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Density Effect and Economic Threshold of Purple Nutsedge (Cyperus rotundus L.) in Peanut (Arachis hypogaea L.) - Long Du; Xiao Li; Jianhong Chen; Xiaojing Jiang; Qian Ju; Chunjuan Qu; Mingjing Qu (International Journal of Plant Production, 2019)

TICKET attracts pollen tubes and mediates reproductive isolation between relative species in Brassicaceae - Jiang-Guo Meng; Meng-Xia Zhang; Wei-Cai Yang; Hong-Ju Li (Science China Life Sciences, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Cytotoxic abietane and kaurane diterpenoids from Celastrus orbiculatus - Wei Jiang; Ti-Zhuang Shan; Jia-Jun Xu; Wen-Ju Chen; Li Miao; Meng-Ying Lv; Li Tao; Yan-Qing Liu (Journal of Natural Medicines, 2019)

Streptomyces monticola sp. nov., a novel actinomycete isolated from soil - Dongmei Li; Liyuan Han; Junwei Zhao; Hanxun Ju; Shanwen Jiang; Xiaowei Guo; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2019)

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor of 30-Day Mortality of Intracerebral Hemorrhage Patients: a Validation Cohort Study - Fei Wang; Li Wang; Ting-ting Jiang; Jian-jun Xia; Feng Xu; Li-juan Shen; Wen-hui Kang; Yong Ding; Li-xia Mei; Xue-feng Ju; Shan-you Hu; Xiao Wu (Neurotoxicity Research, 2018)

Multilayered signaling pathways for pollen tube growth and guidance - Hong-Ju Li; Jiang-Guo Meng; Wei-Cai Yang (Plant Reproduction, 2018)

Spatio-temporal variation of alpine grassland spring phenological and its response to environment factors northeastern of Qinghai-Tibetan Plateau during 2000–2016 - Guangyong Li; Guanghui Jiang; Ju Bai; Cuihong Jiang (Arabian Journal of Geosciences, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

ApoA-I/SR-BI modulates S1P/S1PR2-mediated inflammation through the PI3K/Akt signaling pathway in HUVECs - Kun Ren; Yan-Ju Lu; Zhong-Cheng Mo; Xing -Liu; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Li Li; Qing-Hai Zhang; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2017)

Plant Volatiles Increase Sex Pheromone Attraction of Holotrichia parallela (Coleoptera: Scarabaeoidea) - Qian Ju; Xiao-qiang Guo; Xiao Li; Xiao-jing Jiang; Xiang-guo Jiang; Wan-li Ni; Ming-jing Qu (Journal of Chemical Ecology, 2017)

Optimization of conditions for an integrated multi-trophic aquaculture system consisting of sea cucumber Apostichopus japonicus and ascidian Styela clava - Bao Ju; Ai-li Jiang; Rong-lian Xing; Li-hong Chen; Li Teng (Aquaculture International, 2017)

miR-21 is involved in skeletal deficiencies of zebrafish embryos exposed to polychlorinated biphenyls - Li Ju; Zhiwen Zhou; Bo Jiang; Yue Lou; Zhiqun Zhang (Environmental Science and Pollution Research, 2017)

Thrombospondin-4 Promotes Neuronal Differentiation of NG2 Cells via the ERK/MAPK Pathway - Hai Jie Yang; Shuang Ping Ma; Fei Ju; Ya Ping Zhang; Zhi Chao Li; Bin Bin Zhang; Jun Jiang Lian; Lei Wang; Bin Feng Cheng; Mian Wang; Zhi Wei Feng (Journal of Molecular Neuroscience, 2016)

Microbial community in a multi-trophic aquaculture system of Apostichopus japonicus, Styela clava and microalgae - Jian Lin; Bao Ju; Yanan Yao; Xiaoming Lin; Ronglian Xing; Li Teng; Aili Jiang (Aquaculture International, 2016)

Differential expression of two C‐type lectins in grass carp Ctenopharyngodon idella and their response to grass carp reovirus - C. S. Ju; L. B. He; Y. Y. Pei; Y. Jiang; R. Huang; Y. M. Li; L. J. Liao; S. H. Jang; Y. P. Wang (Journal of Fish Biology, 2016)
The cDNAs of two C‐type lectins in grass carp Ctenopharyngodon idella , galactose‐binding lectin ( galbl ) and mannose‐binding lectin ( mbl ), were cloned and analysed in this study. Both of them exhibited the highest expression level in liver, whereas their expression pattern differed in early phase of embryonic development. Following exposure to grass carp reovirus ( GCRV ), the mRNA expression level of galbl and mbl was significantly up‐regulated in liver and intestine.

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Cisplatin combined with hyperthermia kills HepG2 cells in intraoperative blood salvage but preserves the function of erythrocytes - Jin-ting Yang; Li-hui Tang; Yun-qing Liu; Yin Wang; Lie-ju Wang; Feng-jiang Zhang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2015)

Integrated risk assessment method of waterlog disaster in Huaihe River Basin of China - Ju-Liang Jin; Juan Fu; Yi-Ming Wei; Shang-Ming Jiang; Yu-Liang Zhou; Li Liu; You-Zhen Wang; Cheng-Guo Wu (Natural Hazards, 2015)

Paleoclimate modeling in China: A review - Dabang Jiang; Ge Yu; Ping Zhao; Xing Chen; Jian Liu; Xiaodong Liu; Shaowu Wang; Zhongshi Zhang; Yongqiang Yu; Yuefeng Li; Liya Jin; Ying Xu; et al. (Advances in Atmospheric Sciences, 2015)

Hsa-miR-1246, hsa-miR-320a and hsa-miR-196b-5p inhibitors can reduce the cytotoxicity of Ebola virus glycoprotein in vitro - MiaoMiao Sheng; Ying Zhong; Yang Chen; JianChao Du; XiangWu Ju; Chen Zhao; GuiGen Zhang; LiFang Zhang; KangTai Liu; Ning Yang; Peng Xie; DangSheng Li; et al. (Science China Life Sciences, 2014)

Protective effect of vitexin compound B-1 against hypoxia/reoxygenation-induced injury in differentiated PC12 cells via NADPH oxidase inhibition - Zhong-Bao Yang; Bin Tan; Ting-Bo Li; Zheng Lou; Jun-Lin Jiang; Ying-Jun Zhou; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Protection of MES23.5 dopaminergic cells by obestatin is mediated by proliferative rather than anti-apoptotic action - Xiao-Li Shen; Feng-Ju Jia; Ning Song; Jun-Xia Xie; Hong Jiang (Neuroscience Bulletin, 2014)

S-Adenosylmethionine-induced adipogenesis is accompanied by suppression of Wnt/β-catenin and Hedgehog signaling pathways - Yang Liu; Wentao Lv; Boyang Yu; Tingting Ju; Feiyun Yang; Meihua Jiang; Zuohua Liu; Ling Xu; Wenjuan Sun; Jinxiu Huang; Defa Li; Jingdong Yin (Molecular and Cellular Biochemistry, 2013)

Identification and characterization of antifungal active substances of Streptomyces hygroscopicus BS-112 - Nan Zhang; Zhen Song; Yuhua Xie; Ping Cui; Hongxia Jiang; Tao Yang; Ruicheng Ju; Yuhua Zhao; Jinyu Li; Xunli Liu (World Journal of Microbiology and Biotechnology, 2013)

Screening proteins interacting with VpPR10.1 of Chinese wild grapevine using the yeast two-hybrid system - Teng-Fei Xu; Jiang Xiang; Feng-Ju Li; Tie-Mei Li; Yi-He Yu; Yue-Jin Wang; Yan Xu (Acta Physiologiae Plantarum, 2013)

Effects of indole-3-acetic acid and auxin transport inhibitors on the style curvature of three Alpinia species (Zingiberaceae) - Yin-Ling Luo; Ting-Ju Bi; Dong Li; Zhi-Long Su; Chuan Tao; Yan-Jiang Luo; Qing-Jun Li (Acta Physiologiae Plantarum, 2012)

Streptomyces phytohabitans sp. nov., a novel endophytic actinomycete isolated from medicinal plant Curcuma phaeocaulis - Guang-Kai Bian; Sheng Qin; Bo Yuan; Yue-Ji Zhang; Ke Xing; Xiu-Yun Ju; Wen-Jun Li; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2012)

Molecular characterization and expression analysis of a gene encoding for farnesyl diphosphate synthase from Euphorbia pekinensis Rupr - Xiaoying Cao; Ting Yin; Qian Miao; Changgen Li; Xiuyun Ju; Yong Sun; Jihong Jiang (Molecular Biology Reports, 2012)

Magma mixing origin for the post-collisional adakitic monzogranite of the Triassic Yangba pluton, Northwestern margin of the South China block: geochemistry, Sr–Nd isotopic, zircon U–Pb dating and Hf isotopic evidences - Jiang-Feng Qin; Shao-Cong Lai; Chun-Rong Diwu; Yin-Juan Ju; Yong-Fei Li (Contributions to Mineralogy and Petrology, 2010)

Identification of Sp1-elements in the promoter region of human homeobox gene NKX3.1 - Chun-xiao Yu; Tong Jin; Wei-wen Chen; Peng-ju Zhang; Wen-wen Liu; Heng-yun Guan; Ju Zhang; Qing-wei Liu; An-li Jiang (Molecular Biology Reports, 2009)

Successful implantation of intravenously administered stem cells correlates with severity of inflammation in murine myocarditis - Sohail Malek; Emel Kaplan; Ju-Feng Wang; Qingen Ke; Jamal S. Rana; Yu Chen; Bilal G. Rahim; Ma Li; Qin Huang; Yong-Fu Xiao; Freek W. A. Verheugt; James P. Morgan; et al. (Pflügers Archiv - European Journal of Physiology, 2006)